Beyond the boundaries : a transdisciplinary approach to learning and teaching - Kaufman, Douglas, 1963-; Moss, David M.; Osborn, Terry A., 1966- (Praeger, 2003)
Many contemporary secondary education standards call for teachers to reach across traditional disciplinary lines and create curricula and instructional techniques that are interdisciplinary in nature (as examples, for mathematics see Principles and Standards for School Mathematics; for science see National Science Education Standards; for foreign language see Standards for Foreign Language Learning; Preparing fro the 21st Century). Yet, due to the highly entrenched and fragmented administrative structure of teacher education fields, including tertiary preparation and state certification, most.